Analysis of the functioning and evolution of American exceptionalism - María (Journal of the Basque Parliament, 2022)
In this inquiry, we analyze the characteristics of US presidentialism. Moreover, we use comparisons with parliamentary systems throughout the paper, in order emphasize the singularities of American exceptionalism. In addition to illustrate the advantages and disadvantages of each system, we accentuate the fact that the US President is both the Head of State and the Head of Government. Furthermore, Congress and the President are chosen separately, as a consequence of the separation of powers. Whilst, the former plays a pivotal role in the presidential election. Since the drafting of the US Constitution, more than two hundred years ago, no matter the outcome of the election, the electoral college has brought stability to the presidential system. In addition, the evolution of American democracy has been possible thanks to Constitutional Amendments. As such, the right to vote has evolved throughout the years without the need to draft a new Constitution. Nonetheless, the current polarization purports a threat to the American political systems since it could lead to a regime crisis of American presidentialism. Withal, if the president is to be chosen in a contingent election, Washington DC loses its representation, and state representation is reduced to a single vote per state. For these reasons, the US must undergo necessary changes to update its legal system to the democratic practices of the 21st century.